(untitled) (Eurasian Scientific Herald, 2024)
In this article, the author highlighted scientific ideas about the ability to improve a teacher’s pedagogical skills, ensure the acquisition of knowledge and skills, as well as concepts closer to abilities. In his article, he also stated that it is important to strengthen and modify the teacher’s abilities with the help of psychological technologies in his professional activities.